Late Glacial and Holocene Palaeolake History of the Última Esperanza Region of Southern Patagonia - Roberts, Stephen J.; McCulloch, Robert D.; Emmings, Joseph F.; Davies, Sarah J.; Van Nieuwenhuyze, Wim; Sterken, Mieke; Heirman, Katrien; Van Wichelen, Jeroen; Diaz, Carolina; Van de Vyver, Evelien; Whittle, Alex; Vyverman, Wim; et al. (Frontiers in Earth Science, 2022)
We undertook multiproxy analyses on two sediment core records from Lago Pato, a small lake basin topographically separated from Lago del Toro in Torres del Paine (TdP), to provide insights into glacier dynamics and lake level change in the TdP and Última Esperanza region over the last ~30,000 cal a BP (30 ka). Lago Pato is located at 51°S in a transitional climatic zone of Southern Patagonia sensitive to seasonal to millennial scale changes in the Southern Hemisphere Westerly winds (SWW). Results show that a deep ice dammed palaeolake encompassed Lago del Toro and Lago Pato c. 30–20 ka, after ice had retreated from local-Last Glacial Maximum (l-LGM) limits, c. 48–34 ka, and during the build-up to the global-Last Glacial Maximum (g-LGM), c. 26–19 ka. Gaps in both sediment records between c. 20–13.4 ka and c. 20–10 ka suggest hiatuses in sediment accumulation during the g-LGM and Antarctic Cold Reversal (ACR) readvances and/or removal by lake lowering or flushing during the Late glacial–early Holocene. The palaeolake level dropped from >100 m a.s.l. to ~40–50 m a.s.l. c. 13.4–13.0 ka, towards the end of the ACR, creating a shallower glaciolacustrine environment dammed by an ice tongue in the Estancia Puerto Consuelo–Última Esperanza fjord. This palaeolake remained until the ice thinned to <40–50 m a.s.l. at c. 11.7 ka, isolating Lago Pato from Lago del Toro. At c. 11.7 ka, a shallow, stable and highly anoxic environment developed, and was replaced from c. 10 ka by an increasingly productive shallow-littoral lake with a variable lake-level and periodic shifts in anoxic-oxic bottom water conditions and benthic-planktonic diatoms. An open Nothofagus forest, established at c. 8.6–7.5 ka, and more arid conditions c. 7.5–5.7 cal ka BP are linked to a poleward SWW shift/weakening. More persistently wet conditions from c. 5.7 ka, with extensive closed Nothofagus forests and planktonic diatoms dominant, are associated with equatorward/stronger SWW over 51°S. The abrupt return of benthic-to-tychoplanktonic diatoms after c. 3 ka reflects enhanced SWW at 51°S, while increasingly stable lacustrine and littoral wetland conditions established in the last ~500 years reflects weaker SWW which lasted until recent decades.